2019
DOI: 10.1177/1060028019846654
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Resource Utilization in the Management of Anticholinergic Delirium Between Physostigmine and Nonantidote Therapy

Abstract: Background: Antimuscarinic delirium is associated with significant morbidity, and its management requires substantial resource allocation, including intubation, restraint, and intensive care unit (ICU) placement. There is controversy over the management of these patients. Physostigmine can rapidly reverse antimuscarinic delirium but has been associated with adverse effects. Objective: This study aims to assess the effect of physostigmine use on resource allocation and adverse events. Methods: This is a retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…The clinical literature is characterised by considerable heterogenicity in causative agents, syndrome severity and to a lesser extent physostigmine dosing. [4][5][6][7][8][9][10][11][12][13][14][15] This heterogenicity supports the use of physostigmine in a range of clinical contexts where antimuscarinic delirium is thought likely.…”
Section: Effectivenessmentioning
confidence: 80%
See 3 more Smart Citations
“…The clinical literature is characterised by considerable heterogenicity in causative agents, syndrome severity and to a lesser extent physostigmine dosing. [4][5][6][7][8][9][10][11][12][13][14][15] This heterogenicity supports the use of physostigmine in a range of clinical contexts where antimuscarinic delirium is thought likely.…”
Section: Effectivenessmentioning
confidence: 80%
“…Methodologically these responses span from physician assessment to use of more formal tools to score delirium and agitation. [4][5][6][7][8][9][10][11][12][13][14][15] A number of studies have shown that improvement and resolution of delirium were significantly greater with physostigmine than alternative treatments, most frequently benzodiazepines. Burns reported physostigmine-controlled agitation and reversed delirium in 96% and 87% of patients, respectively, whereas benzodiazepines controlled agitation in 24% of patients but were ineffective in reversing delirium.…”
Section: Effectivenessmentioning
confidence: 99%
See 2 more Smart Citations
“…A more recent retrospective study conducted in 2019 evaluated 141 patients in whom physostigmine was used demonstrated reduced intubation rates without increased incidence of dangerous adverse events including bradycardia and seizures. The study further elucidated that this in turn minimizes critical care time and thus decreases resource utilization in the management of an otherwise complicated patient population [7].…”
Section: Hospital Length Of Staymentioning
confidence: 86%